Knowledge, Attitude and Practice Toward the Coronavirus Disease (COVID-19) Outbreak Among Selected Employed People in the National Capital Region, Philippines - Angelito Bautista Jr.; Dianne Balibrea; Doris G. Bleza (Asian Journal for Public Opinion Research)
COVID-19 has challenged the pandemic response capability of many countries. Many governments around the world have imposed strict quarantine measures and border control to slow the spread of the virus. In the Philippines, the longest community quarantine has been imposed in the National Capital Region (NCR). However, the effectiveness of such measures is dependent on the cooperation of the public. The objective of this study was to gain an understanding of the knowledge, attitudes, and practices (KAP) of selected employees in the NCR. An online survey was conducted June 4-18, 2020, with 100 employed people living in the NCR. Frequencies and percentages were computed to describe the respondents’ answers, and the Kruskal-Wallis test was used to determine the differences in the respondents’ KAP levels according to selected demographic characteristics. Of those surveyed, 92% have a high knowledge of COVID-19. The respondents have a positive attitude toward the need for health education and the seriousness of COVID-19, as well as stricter measures against the pandemic, but are less positive in terms of how the government is responding to the pandemic. They also follow strict measures that will prevent the further spread of the virus. The results highlight the respondents’ favorability of stricter government measures to control the spread of COVID-19, including the re-imposition of an enhanced community quarantine in the NCR.